The Impact of Collective Bargaining on Schools in a Rural Setting: A Retrospective Assessment - Ross A. Engel; David Else (Journal of Research in Rural Education, 1983)
This study was undertaken to assess what had happened to public education in schools located in a primarily rural state seven years after the onset of collective bargaining. A study in 1977 by Harlen Else, conducted two years after the enactment of the law permitting collective bargaining in Iowa, had reviewed the expectations of boards, administrators and teachers at all levels as to what impact bargaining would have on a variety of facets both instructional and non-instructional in the public schools. Now five years leater (1982), David Else has studied essentially the same factors to see what the real effect has been as perceived by the same respondent groups. An oversimplified summary of the findings would indicate that the results have been neither as bad as management groups expected them to be or as good as teacher groups expected them to be. Probably the primary and surprising result is that both management and teachers feel management's control has been strengthened rather than lessened as the result of collective bargaining